A carbon-coated copper-nickel bimetallic catalyst and its preparation method and application
By using carbon-coated copper-nickel bimetallic catalyst, the problems of low hydrogen production rate and poor hydrothermal stability in the hydrogen reforming reaction of ethanol aqueous phase reforming were solved, and a high-load and high-dispersion catalyst structure was achieved, which significantly improved catalytic activity and reaction selectivity.
Patent Information
- Application Number
- CN202510010452.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing catalysts have low hydrogen production rate and short duration in the hydrogen production reaction of ethanol aqueous phase reforming, high cost and poor hydrothermal stability, and low reaction activity of copper-based catalysts and easy deactivation.
A carbon-coated copper-nickel bimetallic catalyst is used. This catalyst forms a highly supported and highly dispersed structure through the complexation of citric acid as a carbon source and a metal compound. The particle size of the copper-nickel metal is controlled at 7~14nm. The activity and stability of the catalyst are improved by calcining and reduction treatment.
It significantly improves the catalytic activity and hydrothermal stability of the catalyst, improves the hydrogen production rate and selectivity of the hydrogen production reaction of ethanol aqueous phase reforming, reduces the preparation cost, and has good industrial application potential.
Smart Images

Figure CN119386875B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more specifically, to a copper-nickel bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] As a green and low-carbon secondary energy, the development of hydrogen energy helps promote the transformation of traditional energy to low-carbon clean energy. As an emerging method of hydrogen production, ethanol aqueous phase reforming can react at low temperatures and requires low energy consumption. At the same time, ethanol as a raw material is cheap and easy to obtain, which greatly reduces the cost of hydrogen production. Therefore, the development of catalysts for ethanol aqueous phase reforming hydrogen production is of great significance.
[0003] Most of the catalysts used in the market for low-temperature ethanol aqueous phase reforming to produce hydrogen are relatively expensive precious metal catalysts, such as catalysts containing metals such as Pt, Pd, Ru, and Rh. However, these catalysts have a low hydrogen production rate and a short reaction duration during the ethanol aqueous phase reforming hydrogen production reaction. In addition, most copper-based catalysts other than precious metal catalysts have low reaction activity and cannot play a good catalytic role in the ethanol aqueous phase reforming hydrogen production reaction. They are also easily deactivated in high temperature environments and have low hydrothermal stability, which limits their application in industrial production.
[0004] Therefore, in the process of ethanol aqueous phase reforming to produce hydrogen, it is particularly important to develop a catalyst with low preparation cost, high selectivity, strong catalytic activity, and good stability under hydrothermal conditions. Summary of the invention
[0005] In view of the above-mentioned deficiencies, the object of the present invention is to provide a carbon-coated copper-nickel bimetallic catalyst having high loading and high dispersibility, as well as higher selectivity and catalytic activity, thereby improving its reaction rate and hydrothermal stability.
[0006] Another object of the present invention is to provide a method for preparing a carbon-coated copper-nickel bimetallic catalyst. The preparation method is simple, and citric acid is used as a carbon source, and no carbonization treatment is required before stirring and mixing with the metal compound.
[0007] Another object of the present invention is to provide an application of the above-mentioned carbon-coated copper-nickel bimetallic catalyst in hydrogen production by aqueous phase reforming of ethanol.
[0008] To this end, the first technical solution provided by the present invention is as follows:
[0009] A carbon-coated copper-nickel bimetallic catalyst, comprising active components Cu and Ni and a carbon carrier coating Cu and Ni;
[0010] Among them: the loading amount of the active component Cu is 20.23-23.53% of the total weight of the catalyst; the loading amount of the active component Ni is 2.13-3.86% of the total weight of the catalyst, and the remainder is the carbon carrier;
[0011] The median particle sizes of the active components Cu and Ni are both 10.9-12.9 nm; and the copper and nickel particles with a particle size of 7-14 nm account for 80%-90% of the weight of the copper and nickel particles in the carbon-coated copper-nickel bimetallic catalyst.
[0012] The contents of the organic carbon carrier and the active components copper and nickel in the carbon-coated copper-nickel bimetallic catalyst of the present invention are relative. When the carbon content is too high, the loading amount of the effective components copper and nickel metals in the catalyst will be reduced, and its reaction rate and selectivity for hydrogen will be inhibited; when the carbon content is too low, the content of copper and nickel metals will be too high, and Cu-Ni will easily agglomerate due to sintering during calcination, and the surface area in contact with the reactants will be reduced, thereby reducing the reaction rate.
[0013] In this case, the particle size of copper and nickel metals is regulated by the organic carbon content and the interaction between active components. The size of active copper nanoparticles, the organic carbon content and their dispersion state jointly affect the catalytic effect of the carbon-coated copper-nickel bimetallic catalyst in ethanol liquid phase hydrogen production. When the copper and nickel metal loading and the organic carbon content reach a relatively stable equilibrium state, the appropriate active component particle size can be obtained, the dispersion of the active component can be improved, and the catalyst activity can be improved.
[0014] When the copper and nickel metals are in the range of 7~14nm, due to the small crystal particle size, the agglomeration of active components can be effectively suppressed, and the copper and nickel metals can be evenly distributed on the carbon coating layer to achieve high dispersion of active components, thereby improving the activity and selectivity of the carbon-coated copper-nickel bimetallic catalyst.
[0015] The second technical solution provided by the present invention is a method for preparing the above-mentioned carbon-coated copper-nickel bimetallic catalyst, comprising the following steps:
[0016] S1. The copper nitrate solution, the nickel nitrate solution and the citric acid are mixed and fully complexed, and then dried to obtain a Cu-Ni-CA complex;
[0017] Wherein, the molar ratio of copper nitrate, nickel nitrate and citric acid is 1: (0.1-0.2): 3;
[0018] S2. calcining the Cu-Ni-CA composite prepared in S1 at 200-600° C. for 1-4 h under an inert gas atmosphere to obtain a carbon-coated copper-nickel bimetallic catalyst precursor;
[0019] S3. The carbon-coated copper-based catalyst precursor is reduced in a hydrogen atmosphere to make the copper active sites evenly distributed on the carbon coating layer to obtain a carbon-coated copper-nickel bimetallic catalyst.
[0020] Furthermore, in the method for preparing the above-mentioned carbon-coated copper-nickel bimetallic catalyst, the molar ratio of the copper salt, the nickel salt and the citric acid in step S1 is 1: (0.1-0.2):3.
[0021] Furthermore, in the preparation method of the carbon-coated copper-nickel bimetallic catalyst, the complexing in step S1 is carried out by stirring at 90° C. for 12 h; and drying at 100° C. for 12 h.
[0022] Furthermore, in the above-mentioned method for preparing the nitrogen-doped carbon-coated copper catalyst, the calcination temperature in step S2 is 300-500° C., and the calcination time is 2-3 h.
[0023] Furthermore, in the above-mentioned method for preparing the carbon-coated copper-nickel bimetallic catalyst, the reduction temperature in step S3 is 250-550°C.
[0024] The carbon-coated copper-nickel bimetallic catalyst of the present invention uses citric acid provided by citric acid as a carrier to fix the active components of copper and nickel metals, so that they can achieve high loading and high dispersion in citric acid, effectively preventing Cu-Ni from agglomerating due to sintering, thereby improving its reaction rate and hydrothermal stability.
[0025] The last technical solution provided by the present invention is that the carbon-coated copper-nickel bimetallic catalyst is used to catalyze the reaction of ethanol aqueous phase reforming to produce hydrogen.
[0026] The present invention uses citric acid (CA) as an organic carbon source. The carboxyl functional groups contained in the citric acid can effectively coordinate with the copper-nickel metal particles, easily form a complex, and have a good dispersion effect on the active components of copper and nickel metals, which can prevent the migration of active components during the calcination process from causing insufficient dispersion. In addition, the citric acid calcined in an inert atmosphere will form a carbon layer, which can effectively coat the copper and nickel metals, provide attachment sites for the active components, form a high-load and high-dispersion structure, and make the catalyst have better catalytic performance.
[0027] In the present invention, the particle size, active component loading and carbon content of copper and nickel metals are all affected by the ratio of Cu, Ni and citric acid. Therefore, in order to obtain the carbon-coated copper-nickel bimetallic catalyst described in the present invention, it is necessary to reasonably control the ratio of copper nitrate, nickel nitrate and citric acid, so that the active components can be well dispersed under high load conditions, the particle size can be stabilized at a small particle size, and in the case of high-density active components, the migration of active components during the reduction process of S2 can be further prevented to cause agglomeration.
[0028] The present invention ensures that the loading ratio of carbon to copper and nickel metals is appropriate by adjusting the calcination conditions, thereby avoiding the problem of agglomeration of active components due to excessively high temperature or insufficient carbon content due to excessively low temperature.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] 1. The carbon-coated copper-nickel bimetallic catalyst provided by the present invention has inorganic copper salt solution, inorganic nickel salt solution and carbon-containing organic matter as its main components. The carbon layer is used to effectively restrain the migration and agglomeration of the active components of copper and nickel metals, while providing abundant attachment sites to achieve a high-load and highly dispersed carbon-coated structure. By precisely controlling the loading amount, carbon content and particle size of the active components, the catalytic performance of the catalyst is significantly improved, showing excellent catalytic activity and excellent hydrothermal stability.
[0031] 2. The carbon-coated copper-nickel bimetallic catalyst provided by the present invention improves the activity of the catalyst by adding inorganic nickel salts to common copper-based catalysts, and adds citric acid as citric acid to fix the active component Cu-Ni, and controls the ratio of citric acid, copper salt and nickel salt. On the premise of ensuring that the carbon-coated copper-nickel bimetallic catalyst is stable under hydrothermal conditions and can effectively improve the hydrogen production rate, it accelerates the speed at which the catalyst reaches its peak hydrogen production performance and further optimizes its catalytic efficiency.
[0032] 3. The preparation method of the catalyst provided by the present invention is simple, and citric acid is used as the carbon source. No carbonization treatment is required before stirring and mixing with the metal compound. By controlling the reaction conditions, the obtained carbon-coated copper catalyst has the characteristics of small particle size, high load and high dispersion, and can achieve the effects of high hydrogen production rate, strong hydrogen selectivity and high catalytic activity. It can be used for rapid production of high-purity hydrogen, and is particularly suitable for the field of ethanol aqueous phase reforming hydrogen production.
[0033] 4. The carbon-coated copper-nickel bimetallic catalyst provided by the present invention has low cost in the production of hydrogen by aqueous phase reforming of ethanol and is expected to become a substitute for precious metal catalysts; it also has good selectivity and catalytic activity, and the hydrogen production rate of the reaction at 220°C is greater than 37.21 μmol·gcat -1 ·s -1 The selectivity of hydrogen is 90.33%, and the selectivity of carbon monoxide is less than 9.74%, which can ensure long-term continuous and stable operation of ethanol aqueous phase reforming hydrogen production; it is conducive to the realization of efficient ethanol aqueous phase reforming hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is the infrared spectrum of the carbon-coated copper-nickel bimetallic catalyst provided in Example 1.
[0035] Figure 2This is a scanning electron microscope (SEM) image of the carbon-coated copper-nickel bimetallic catalyst provided in Example 1.
[0036] Figure 3 This is the HRTEM image corresponding to the carbon-coated copper catalyst provided in Example 1.
[0037] Figure 4 The high-angle annular dark field transmission electron microscope image of the carbon-coated copper-nickel bimetallic catalyst provided in Example 1 and the enlarged HRTEM image of the carbon layer-coated copper and nickel metal structure.
[0038] Figure 5 This is a particle size analysis chart of the carbon-coated copper-nickel bimetallic catalyst provided in Example 1.
[0039] Figure 6 This is the elemental analysis diagram of the carbon-coated copper-nickel bimetallic catalyst provided in Example 1.
[0040] Figure 7 This is a comparison chart of the performance of carbon-coated copper-nickel bimetallic catalyst Ni commercial catalyst with different ratios for ethanol aqueous phase reforming hydrogen production.
[0041] Figure 8 XRD spectra of carbon-coated copper-nickel bimetallic catalysts with varying molar ratios of copper nitrate to nickel nitrate. DETAILED DESCRIPTION
[0042] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0043] Example 1
[0044] This embodiment provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen, which is prepared by the following steps:
[0045] S1. Copper nitrate, nickel nitrate and citric acid were mixed and stirred at 90°C for 12 hours for full complexation, and then fully dried at 100°C for 12 hours to obtain a Cu-Ni-CA complex;
[0046] Wherein, the molar ratio of copper nitrate to nickel nitrate is 1:0.11:3;
[0047] S2. The Cu-Ni-CA complex in S1 was calcined at 400°C for 2 h under a nitrogen atmosphere to obtain a carbon-coated copper-nickel bimetallic catalyst precursor;
[0048] S3. 30 mg of carbon-coated copper catalyst precursor was reduced at 350° C. for 2 h at a hydrogen flow rate of 50 ml / min to obtain a carbon-coated copper-nickel bimetallic catalyst. The components and their contents in the catalyst are shown in Table 1.
[0049] By infrared spectroscopy analysis of the raw material Cu-Ni@CA composite, refer to Figure 1 , judging that the carboxyl group in citric acid coordinates with copper and nickel metals to form a complex. Through infrared spectrum observation, the broad peak formed in the wave number range of 3300-2500cm⁻¹ is the carboxyl peak, proving that the effective components copper and nickel metals may coordinate to form a complex through the oxygen-containing functional group COOH in citric acid, so that copper and nickel metals can be evenly distributed on the citric acid derived from citric acid, and are not easy to agglomerate due to sintering during the calcination process.
[0050] For the SEM images of the carbon-coated Cu-Ni bimetallic catalyst and the corresponding HRTEM images of the carbon-coated Cu catalyst, please refer to Figure 2 and Figure 3 ; Through SEM observation, the carbon-coated copper-nickel bimetallic catalyst is loose and porous inside, has a large specific surface area, can effectively contact the reactants in the ethanol water-phase reforming hydrogen production reaction, and has a high hydrogen production rate. From the HRTEM image of the carbon-coated copper-nickel bimetallic catalyst, it can be seen that the copper and nickel metals are evenly distributed on the organic carbon layer derived from citric acid, and have good dispersibility while meeting the high loading rate, without obvious agglomeration, with high reaction activity, and can effectively catalyze the ethanol water-phase reforming hydrogen production reaction.
[0051] High-angle annular dark field transmission electron microscopy (HAADF-STEM) image of carbon-coated copper-nickel bimetallic catalyst and magnified HRTEM image of copper and nickel metal structures coated with carbon layer, see Figure 4 It can be seen that the carbon-coated copper-nickel bimetallic catalyst has a higher number of active sites, and the effective components of copper and nickel metals are fixed by citric acid derived from citric acid, with a particle size of about 12 nm, which is conducive to full contact with the reactants in the ethanol aqueous phase reforming hydrogen production reaction and improves its hydrogen production rate.
[0052] Particle size analysis of carbon-coated copper-nickel bimetallic catalyst, see Figure 5 It can be seen that the effective components of the carbon-coated copper-nickel bimetallic catalyst, copper and nickel metal particles, have relatively small particle sizes, with a median particle size of 11.692 nanometers, and copper and nickel metal particles with a particle size of 7 to 14 nm account for 80% to 90% of the carbon-coated copper-nickel bimetallic catalyst.
[0053] Elemental analysis (EDS mapping) of carbon-coated copper-nickel bimetallic catalyst, see Figure 6It can be seen that the loading rate of the effective components copper and nickel metals in the carbon-coated copper-nickel bimetallic catalyst is relatively high, and the copper and nickel metals are evenly embedded in the organic carbon layer derived from citric acid. It can be seen that the carbon-coated copper-nickel bimetallic catalyst has good reaction activity.
[0054] Example 2
[0055] This embodiment provides another carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature in S2 is 300°C and the calcination time is 2h. Please refer to Table 1 for the components and contents of the catalyst.
[0056] Example 3
[0057] This embodiment provides another carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature in S2 is 500°C and the calcination time is 2h. Please refer to Table 1 for the components and contents of the catalyst.
[0058] Example 4
[0059] This embodiment provides another carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature in S2 is 400°C and the calcination time is 3h. Please refer to Table 1 for the components and contents of the catalyst.
[0060] Example 5
[0061] This embodiment provides another carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature in S2 is 400°C and the calcination time is 1 h. Please refer to Table 1 for the components and contents of the catalyst.
[0062] Example 6
[0063] This embodiment provides another carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature in S2 is 300°C and the calcination time is 1 h. Please refer to Table 1 for the components and contents of the catalyst.
[0064] Example 7
[0065] This embodiment provides another carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature in S2 is 300°C and the calcination time is 3h. Please refer to Table 1 for the components and contents of the catalyst.
[0066] Example 8
[0067] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate, nickel nitrate and citric acid is 1:0.1:3. Please refer to Table 1 for the components and their contents in the catalyst.
[0068] Example 9
[0069] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate, nickel nitrate and citric acid is 1:0.2:3. Please refer to Table 1 for the components and their contents in the catalyst.
[0070] Table 1
[0071] Copper nanoparticle loading / wt% Nickel nanoparticle loading / wt% Carbon content / wt% Median particle size of copper and nickel particles / nm Example 1 22.03 2.25 75.72 11.7 Example 2 21.95 2.19 75.86 11.2 Example 3 23.48 2.32 74.20 12.5 Example 4 23.53 2.29 74.18 12.7 Example 5 21.99 2.17 75.84 11.6 Example 6 21.78 2.13 76.09 11.4 Example 7 22.97 2.21 74.82 11.8 Example 8 22.01 2.20 75.79 10.9 Example 9 20.23 3.86 75.91 12.9
[0072] Comparative Example 1
[0073] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that nickel nitrate is not added in this comparative example, and the molar ratio of copper nitrate to citric acid is 1:3. Please refer to Table 2 for the components and contents of the catalyst.
[0074] Comparative Example 2
[0075] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate, nickel nitrate and citric acid is 1:0.25:3. Please refer to Table 2 for the components and their contents in the catalyst.
[0076] Comparative Example 3
[0077] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate, nickel nitrate and citric acid is 1:0.5:3. Please refer to Table 2 for the components and their contents in the catalyst.
[0078] Table 2
[0079] Copper nanoparticle loading / wt% Nickel nanoparticle loading / wt% Carbon content / wt% Median particle size of copper and nickel particles / nm Comparative Example 1 22.53 0 77.47 10.5 Comparative Example 2 21.43 4.92 73.65 13.1 Comparative Example 3 19.48 9.41 71.11 14
[0080] Note: The copper nanoparticle loading described in this application refers to metallic copper, and the total mass of copper in cuprous oxide accounts for the total mass percentage of the catalyst.
[0081] Comparative Examples 4 to 8
[0082] Comparative Examples 4 to 8 provide a carbon-coated copper-nickel bimetallic catalyst for hydrogen production by aqueous phase reforming of ethanol, the preparation method of which is basically the same as that of Example 1, except that the carbon source is different, see Table 3 for details.
[0083] Table 3
[0084] Comparative Example Organic carbon source Comparative Example 4 glucose Comparative Example 5 Sorbitol Comparative Example 6 Agar Comparative Example 7 Konjac Gum Comparative Example 8 Agarose
[0085] Comparative Example 9
[0086] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature used is 200°C and the calcination time is 2h. Please refer to Table 3 for the components and their contents in the catalyst.
[0087] Comparative Example 10
[0088] This comparative example provides a carbon-coated copper-nickel bimetallic catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature used is 600°C and the calcination time is 2h. Please refer to Table 3 for the components and their contents in the catalyst.
[0089] Comparative Example 11
[0090] The purchased Raney Ni commercial catalyst was ground and crushed, and 30 mg of the catalyst was weighed and reduced at 350° C. for 2 h at a hydrogen flow rate of 50 ml / min.
[0091] Results
[0092] The catalytic reaction conditions of the carbon-coated copper catalyst in ethanol aqueous phase reforming to produce hydrogen are as follows:
[0093] 25 mg of any one of the catalysts described in Examples 1-9 and Comparative Examples 1-11 was added to 20 ml of ethanol aqueous solution in a batch reactor, and 2 MPa argon was used as a protective gas. After reacting at 220° C. for 2 h, the gas phase product was quantitatively analyzed by gas chromatography after cooling to room temperature. The results are shown in Table 4.
[0094] The ethanol aqueous solution is composed of ethanol and water in a molar ratio of 1:1.
[0095] The hydrogen production rate of the carbon-coated copper catalyst is calculated by the water displacement method based on the gas production volume. The hydrogen production rate is the μmol hydrogen content produced per gram of catalyst per second. The selectivity is calculated by the amount of H2, CO, and CH4 in the product, for example, hydrogen selectivity H2 (%) = nH2*100% / (nH2+nCO+nCH4).
[0096] Table 4 Comparison of catalytic effects of various embodiments and comparative examples
[0097]
[0098] From Examples 1 to 3, Comparative Examples 9-10 and Table 4, it can be seen that when the calcination temperature varies in the range of 200°C to 600°C, the catalyst obtained by calcination at 400°C has the best performance, indicating that the calcination temperature of 400°C can promote the formation of sufficient pores inside the carbon-coated copper-nickel bimetallic catalyst, increase the specific surface area and active sites, and thus make the catalyst have higher activity. However, the copper nanoparticles in the carbon-coated copper catalyst calcined at 200°C are difficult to disperse, and the catalytic rate is low; the copper and nickel metals in the carbon-coated copper-nickel catalyst calcined at 600°C agglomerate, the particle size increases, resulting in a smaller effective area of the catalyst and a lower reaction rate.
[0099] It can be seen from Example 1, Example 8, Example 9 and Comparative Examples 1 to 3 that the performance of the catalyst is different when the ratio of nickel nitrate added is changed. The XRD spectra of the carbon-coated copper-nickel bimetallic catalyst with a different molar ratio of copper nitrate to nickel nitrate are shown in FIG. Figure 8 . As can be seen from the figure, as the molar ratio of Ni to Cu increases from 0 to 1:2, the sharpness of the characteristic peak of copper presented in the XRD spectrum decreases, indicating that the incorporation of nickel effectively inhibits the agglomeration of copper active sites, increases the effective contact area between the catalyst and ethanol water, and can greatly improve the catalyst effect. In the process of adjusting the ratio of Cu to Ni from 1:0.11 to 1:0.5, the characteristic peak of copper decreases significantly, indicating that when the nickel doping amount is too much, the activity of copper will be inhibited, which will also lead to a decrease in hydrogen production rate and selectivity.
[0100] The hydrogen production rate of the catalyst without nickel nitrate is lower than that of the catalyst with nickel. However, when the amount of nickel nitrate added is too much, nickel will occupy most of the active sites, destroying the synergistic effect between copper and nickel metals, and the hydrogen production rate will decrease. At the same time, the large amount of nickel added increases the reactivity of nickel for the side reaction reverse water gas shift reaction (RWGS), resulting in further hydrogenation of the byproduct carbon dioxide into carbon monoxide, reducing the selectivity of the ethanol aqueous phase reforming hydrogen production reaction.
[0101] It can be seen from Example 1 and Comparative Examples 4 to 8 that the hydrogen production performance of the catalyst prepared by using citric acid as an organic carbon source is better than that of other catalysts such as sorbitol or glutamic acid as organic carbon sources. This is because the addition of citric acid enriches the pore structure of the catalyst, making the catalyst have a higher dispersion of metal active components and a more uniform particle size of active components. In addition, the carboxyl groups in citric acid produce complexation with metal ions, effectively preventing the agglomeration of copper and nickel metals during the calcination process, thereby improving the dispersibility and activity of the catalyst.
[0102] From Table 4 and Figure 7 It can be seen that the hydrogen production rate of the carbon-coated copper-nickel bimetallic provided in the present application at 220°C is greater than 37.21 μmol·gcat -1 ·s -1 The selectivity of hydrogen is 90.33%, and the selectivity of carbon monoxide is less than 9.74%. The performance is significantly better than that of Raney Ni commercial catalyst, which is conducive to the realization of efficient hydrogen production by ethanol aqueous phase reforming.
[0103] It should be noted that although the other embodiments do not provide relevant descriptions of their corresponding XRD spectra, transmission electron microscope images, and elemental analysis diagrams, their relevant performances are equivalent and therefore omitted.
[0104] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. Application of a carbon-coated copper-nickel bimetallic catalyst in hydrogen production from ethanol aqueous phase reforming, characterized in that: The carbon-coated copper-nickel bimetallic catalyst comprises active components Cu and Ni, and a carbon carrier coating Cu and Ni; Wherein: the loading amount of the active component Cu is 20.23-23.53% of the total weight of the catalyst, the loading amount of Ni is 2.13-3.86% of the total weight of the catalyst, and the remainder is the carbon carrier; The median particle size of the active components Cu and Ni is 10.9-12.9 nm; and the Cu and Ni particles with a particle size of 7-14 nm account for 80%-90% of the total weight of the Cu and Ni particles in the carbon-coated copper-nickel bimetallic catalyst; The preparation method of the carbon-coated copper-nickel bimetallic catalyst comprises the following steps in sequence: S1. The copper nitrate solution, the nickel nitrate solution and the citric acid are mixed and fully complexed, and then dried to obtain a Cu-Ni-CA complex; S2. calcining the Cu-Ni-CA complex prepared in S1 at 300-500° C. for 2-4 h under an inert gas atmosphere to obtain a carbon-coated copper-nickel bimetallic catalyst precursor; S3. The carbon-coated copper-nickel bimetallic catalyst precursor prepared in S2 is reduced in a hydrogen atmosphere, so that the active components Cu and Ni are embedded in the carbon coating layer to obtain a carbon-coated copper-nickel bimetallic catalyst; In step S1, the molar ratio of copper nitrate, nickel nitrate and citric acid is 1:(0.1-0.2):
3.
2. The use of the carbon-coated copper-nickel bimetallic catalyst in hydrogen production from ethanol aqueous phase reforming according to claim 1, characterized in that: Add 25 mg of carbon-coated copper-nickel bimetallic catalyst to 20 mL of ethanol aqueous solution in a batch reactor, use 2 MPa argon as protective gas, react at 220°C for 2 h, and then use gas chromatography to quantitatively analyze the gas phase product after cooling to room temperature.
3. The use of the carbon-coated copper-nickel bimetallic catalyst in ethanol aqueous phase reforming hydrogen production according to claim 2, characterized in that: The ethanol aqueous solution consists of ethanol and water in a molar ratio of 1:
1.
4. The use of the carbon-coated copper-nickel bimetallic catalyst in hydrogen production from ethanol aqueous phase reforming according to claim 1, characterized in that: The complexing in step S1 is carried out by stirring at 90° C. for 12 h; and the drying is carried out by drying at 100° C. for 12 h.
5. The use of the carbon-coated copper-nickel bimetallic catalyst in hydrogen production from ethanol aqueous phase reforming according to claim 1, characterized in that: The reduction temperature in step S3 is 250-550°C.
Citation Information
Patent Citations
Catalyst for water vapor reformation of ethanol to prepare hydrogen and its prepn and use
CN101020141A
Carbon-coated copper material and preparation method and application thereof
CN114984952A
Carbon-coated non-noble metal alloy nanoparticle catalyst as well as preparation method and application thereof
CN117123771A